Up-to-date review of psychotherapy via videoconference: implications and recommendations for the RANZCP Psychotherapy Written Case during the COVID-19 pandemic. (October 2020) - Chherawala, Nabil; Gill, Shane
Objective: There has been a surge in videoconferencing technology use in response to the COVID-19 pandemic. RANZCP registrars engaged in the Psychotherapy Written Case are met with new challenges in navigating the psychodynamic processes that can occur when transitioning from in-person to videoconferencing psychotherapy. There is also a myriad of videoconferencing platforms to choose from. Conclusion: It has become necessary to adapt our clinical practice to the current COVID-19 pandemic and physical distancing regulations. The literature recognises videoconferencing psychotherapy as a valid therapeutic medium which can facilitate healthy psychological maturation, but there are theoretical drawbacks. A transition to videoconferencing psychotherapy requires patient agreeability, consistency and reflection upon patient–therapist dynamics; this will aide in the Psychotherapy Written Case submission. Registrars must balance usability, digital security and patient preferences when choosing videoconferencing platforms.